Das Adenauer-Komplott - Thiel, Sebastian (GMEINER, 2017)
Handelt im Köln des Jahres 1944
urn:nbn:de:101:1-201704011854
Keywords: (Produktform)Electronic book text; Nordrhein-Westfalen; Köln; Zeitgeschichte; Kanzler; Wehrmacht; Pilot; Flucht; (VLB-WN)9121: NONBOOK/Belletristik/Krimis; Thriller; Spionage; (Zielgruppe)Kinder/Jugendliche; (Lesealter)ab 16 Jahre